2000
DOI: 10.1097/00004770-200002000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic Considerations of the Nasopalatine Duct Region

Abstract: Although rare, anomalies of the nasopalatine region have been reported in the literature mimicking pathoses of endodontic origin. The purpose of this article is to present a case of a patent nasopalatine duct that was originally diagnosed as a sinus tract and referred for endodontic therapy. A review of the anatomy of the nasopalatine region is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
1
10
0
5
Order By: Relevance
“…2G-J). Similar clinical, radiographic, and histopathological findings have been reported in other cases (4)(5)(6)(7)(8)(9)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…2G-J). Similar clinical, radiographic, and histopathological findings have been reported in other cases (4)(5)(6)(7)(8)(9)(27)(28)(29)(30)(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 82%
“…Clinical examination showed that anterior teeth were vital (pulp vitality test). has a less aggressive behavior, low recurrence rates, and limited growth (25,(28)(29)(30)(31)(32)(33)(34). The optimal approach to the treatment of NPDC is surgical enucleation because of its cyst-like features (25,(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…It is attributed to a number of causes such as infection, retention phenomenon of the blocked mucous glands, epithelial remnants of the Jacobson's organ, trauma, ill-fitting dentures or idiopathic 1. Owing to its location NPDC is often mistaken for several other pathological entities which may occur in this region such as a large incisive fossa, radicular cyst, dentigerous cyst arising from a mesiodens, oronasal fistula, oroantral fistula, chronic draining dentoalveolar abscess with sinus tract 3. The clinical implications and the treatment options vary depending on the nature of each of these entities necessitating the importance of accurate diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The anterior maxilla region is being referred by the former report as the “traumatic zone” (Tolstunov 2007); Daley et al (1994) found 73% of 295 cases involving nonodontogenic tumors were nasopalatine duct cysts. Yet there are poorly documented anatomical variations in dimensions and morphology of this canal (Chandler & Gray 1996, Jacob et al 2000, Moss et al 2000). Though, with the increasing demand for rehabilitation of the edentulous maxilla by means of osseointegrated implants, pre‐operative evaluation of the nasopalatine canal region has regained attention (Kraut & Boyden 1998, Cavalcanti et al 1999, Artzi et al 2000).…”
mentioning
confidence: 99%